Congenital Toxoplasmosis presenting as multiple ring enhancing lesions in brain on neuroimaging - Thakkar, Pareshkumar A.; Shah, Aakashi; Javadekar, Bakul B.; Modasia, Saurabh (International Journal of Contemporary Pediatrics, 2018)
We report a case of congenital toxoplasmosis in a male child who presented at 1 month 21 days of life. He had a past history of meningitis on third day of life which resolved with intravenous antibiotics. This time, the child presented with progressive enlargement of head and CSF (Cerebrospinal fluid) showed elevated protein levels with cellular reaction and CT scan showed dilated ventricular system with aqueductal obstruction and multiple ring-enhancing lesions in bifrontal and bioccipital regions with a right porencephalic cyst. Repeat CSF after 14 days of intravenous antibiotics showed elevated protein with no cellular reaction. Fundus examination was normal. Toxoplasma blood serology (IgG and IgM) in baby and mother were positive. The child received treatment with Pyrimethamine, Clindamycin, Folinic acid and Prednisolone. CSF parameters got normalized and multiple ring-enhancing lesions disappeared on repeat CT scan. He underwent a Ventriculo-Peritoneal shunt surgery for the hydrocephalus and was discharged in a stable condition.